Gendered Readings of the First World War: A European Overview - Balogh, Eszter Edit (Hungarian Journal of English and American Studies, 2020)
Book review:Hämmerle, Christa, Oswald Überegger, and Birgitta Bader Zaar, eds. Gender and the First World War. Hampshire, NY: Palgrave Macmillan, 2014. 265 pages. ISBN 978-1-137-30219-9. Hb. $100.